Pengaruh Tunjangan Kinerja, Pelatihan, Kedisiplinan Dan Dukungan Organisasi Terhadap Loyalitas Kerja Pegawai - Arnice Malanuwa; Meimoon Ibrahim; Yakup Yakup; Deby R. Karundeng (Journal Economy and Currency Study (JECS), 2023)
The purpose of this study was to analyze the effect of performance allowances, training, discipline and organizational support on employee work loyalty at the Community and Village Empowerment Service). The data used in this study is primary data sourced from filling out questionnaires. The research population is 65 respondents using the census method. The analytical technique used to answer research problems and test hypotheses is multiple regression analysis. The findings of this study are (1) performance allowances have a positive and significant effect on work loyalty, (2) training has a positive and significant effect on work loyalty, (3) work discipline has a positive and significant effect on work loyalty, (4) organizational support has a positive and no effect significant effect on work loyalty.